Authorship characteristics in the ASLP Bulletin and the Journal of Philippine Librarianship - Rico, Joy R. (Institute of Library Science, University of the Philippines Diliman, 1998)
The ASLP Bulletin and the Journal of Philippine Librarianship are two periodicals that have made a significant impact in Philippine librarianship. This bibliometric survey made on the authors who got their articles published in two periodicals focused on the characteristics such as sex, geographic distribution and occupational category.